Aortic dissection albeit negative d-dimers and zero clinical probability – Another facet of medicine's deadly chameleon. Issue 2 (February 2017) - Ruf, Tobias Friedrich; Pfluecke, Christian; Mues, Christoph; Strasser, Ruth H.
Abstract: Aortic dissection, the rupture of the aorta's intimal and medial layers, leading to the formation of a false lumen, is a relatively common disease with high mortality. So far, while not addressing penetrating aortic ulcer or intramural hematoma, current guidelines take a negative value ford -dimers for a sufficient method to rule out aortic dissection in patients with a low clinical probability, as calculated by the ADD risk score. We present two cases of patients with acute aortic dissection, albeit presenting with a low clinical probability for acute aortic dissection and negative values ford -dimers. <Learning objective: One must entertain a high level of suspicion for acute aortic syndrome as even laboratory results within the normal range ofd -dimers connected with a low clinical probability can be misleading. According to the patient's symptoms, a battery of different diagnostic tools should play in concert, including imaging studies, repeat clinical evaluation, and repeat laboratory tests, such asd -dimers, before dismissing a diagnosis as severe as aortic dissection.>